Sosialisasi Cara Mencuci Tangan Di SDN 1 Sukajadi Dalam Upaya Mencegah Penyakit Diare di Musim Penghujan - Wahyiah, Ita Rosita; Muhidin, Cecep (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2024)
KKM Group 63 Sukajadi Village, Carita Sub-district, Pandeglang Regency socialises proper hand washing in an effort to prevent diarrhoea, a health problem that often occurs, especially during the rainy season. This service aims to analyse the impact of the socialisation of good and correct hand washing on students of SDN 1 Sukajadi in an effort to prevent diarrhoeal diseases. The method used is a participatory approach by providing education, demonstration, and observation of student hand washing behaviour before and after socialisation. The results showed a significant increase in knowledge and handwashing practices in students after socialisation. This indicates that socialisation is an effective intervention to improve clean and healthy living behaviour and prevent diarrhoea among students.